PENENTUAN LOKASI SMA NEGERI MENGGUNAKAN DIAGRAM VORONOI BERBOBOT DI KOTA DENPASAR - HERMANTO, MELINDA; OKA, TJOKORDA BAGUS; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika; Vol 2 No 2 (2013), 2013)
In school development problem, determining location is one of important things to consider. In this research, the purpose is to determine the location of SMAN 9 Denpasar if it will be built. One of algorithms in computational geometry that can be used to find solution of facility location problem is multiplicatively weighted Voronoi diagram in two dimensions. The result of weighted Voronoi diagram shows the influence of each site to the surrounding area. Then, the location of SMAN 9 Denpasar is obtained by determining the center of the largest empty circle of the weighted Voronoi diagram.
Keywords: facility location problem; weighted Voronoi diagram; computational geometry